A Decade of Artificial Intelligence (AI) and Geography: Bibliometric Insights with AI-Powered Analysis - Oğlakcı , Burak; Uzun, Alper (European Journal of Geography, 2025)
In the last decade, there has been a significant increase in the number of geography studies utilizing artificial intelligence (AI) applications and algorithms. Despite this increase, what is known about related studies is limited. The study aims to reveal the current state, trends, themes, and collaborations of the studies carried out in the interaction of AI and geography in the last decade and to highlight the prospects of AI within geography. Accordingly, the study is based on the bibliometric data of geography studies that have AI applications and algorithms. In the analysis of the data, basic analyses were first conducted covering titles, abstracts, keywords, and so on. Topic modelling was performed using the BERTopic to identify the research themes. Additionally, natural language processing (NLP) tasks were utilized to enhance the efficiency of the analysis. Between 2015 and 2024, productivity in the interaction of geography and AI has shown a significant increase, with 124 different countries contributing to this productivity. This reflects a growing global interest in the field. With increasing interest and productivity, it has been concluded that the methodologies, data, and focal topics have evolved and diversified, while the number of collaborations has also increased. The role of AI in geography is expected to become even more prominent in the future, thanks to its advanced data processing capacity, real-time analysis capabilities, and complex spatial modelling skills. However, soon, some specific approaches and issues (ethical and technical) regarding the interaction between geography and artificial intelligence are noteworthy. Highlights: AI and geography research expanded globally, with 124 countries contributing. AI has evolved and diversified geography research methods, data, and focal topics. The role of AI in geography is expected to become more prominent. Ethical and technical issues in geography-AI interaction require urgent attention.